Effects of tides, waves, and sea dikes on storm surge-induced coastal flooding in the Thanh Hoa region - Pham, Van Tien; Nguyen, Ba Thuy; Nguyen, Kim Cuong; Vu, Hai Dang; Bui, Manh Ha; Nguyen, Phuong Anh; Kim, Sooyoul; Hole, Lars Robert (Vietnam Journal of Marine Science and Technology, 2026)
In this study, the impacts of tides, ocean waves, and sea dikes on coastal flooding in Thanh Hoa Province caused by storm surge in combination with tides were evaluated using simulated flooding results for Typhoon Doksuri (September 2017). The simulations were conducted with the SuWAT numerical model, in which tide, wave, and storm surge processes were integrated. The SuWAT model was developed using a moving-boundary algorithm to simulate flooding driven by tidal variations and storm surges. The results indicate that, for Typhoon Doksuri (September 2017), when the typhoon landfall occurred during the highest tidal phase, the total inundated area in the study region increased by approximately 21.9% compared with the landfall time during the lowest tidal phase. When wave-induced effects were included in the model, the inundated area increased by about 7.2% relative to the case without wave influence. In the scenario without sea dikes along the Thanh Hoa coast, the total flooded area increased by approximately 69.0% compared to the case with real existing dikes. These findings provide valuable insights for coastal zone planning and for improving flood forecasting and early warning systems related to tidal and storm surge-induced flooding in the study area.